2009
DOI: 10.4103/0973-3930.57347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combined resistance and home-based walking exercise in type 2 diabetes patients

Abstract: Aims:The aim of this study was to evaluate the effect of combined resistance and home-based walking exercise on glycemic and metabolic control, depression and quality of life in type-2 diabetes patients.Methods:This prospective study was conducted at a private hospital in Turkey. Thirty-six type-2 diabetic patients participated in the study. Subjects were randomly distributed in one 8 week exercise intervention or in one control group. Exercise program consisted of resistance training and home-based walking. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 34 publications
1
49
2
Order By: Relevance
“…[25] Despite these benefits, literature states that many patients with diabetes have stopped exercise programs. [30] However, in the present study, we found an increase in the proportion of patients who began to take adequate physical exercise (at least 30 min) after the education program.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…[25] Despite these benefits, literature states that many patients with diabetes have stopped exercise programs. [30] However, in the present study, we found an increase in the proportion of patients who began to take adequate physical exercise (at least 30 min) after the education program.…”
Section: Discussioncontrasting
confidence: 66%
“…[3031] Exercise increases insulin sensitivity (both short and long term), lowers blood sugar levels and reduces body weight. [25] Blood glucose levels can significantly drop during and after physical activities because of the increased utilization of glucose as a fuel during exercise and the up-regulation of glucose transport into the working muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies presented exercise interventions developed with exercise machines, such as ergometers for aerobic exercise (treadmills, stationary bikes, rowing machines, steppers, and ellipticals) and/or resistance machines for resistance exercise. Among the published literature, few studies [ 35 , 36 ] have developed combined exercise programs for people with T2D exclusively with low-cost exercise strategies and using different exercise protocols that combine free walking with resistance exercises performed with bodyweight, elastic bands, and free weights, as well as stretching exercises. However, the effects on glycemic control and cardiovascular risk factors were not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Aylin et al [ 36 ] observed a significant improvement in the HbA1c levels of a group of patients with T2D ( n = 18; 51.39 ± 2.02 years of age; HbA1c 7.7 ± 0.4 %; BMI 28.45 ± 0.95 kg/m 2 ; polymedicated; exercise adherence of 96 %) in comparison to a control group after an exercise program of only eight weeks comprising free walking (60–79% maximum heart rate) two days a week, and resistance exercises performed with bodyweight and free weights on two other days. However, no changes were observed in FPG, lipid profile, or BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicated that sports could increase body sensitivity to insulin and reduce FBS and control of the diabetes. [ 20 21 ] However, most of the patients conventionally are reducing their sport and exercises after disease[ 22 ] but in our study, 65% of the patients engaged themselves in a 2 h of exercise per week had controlled disease. We have to consider the destruction of red blood cells as one of the reasons for lower HbA1c measurement, which can lead to missing identification and control of the disease in diabetic patients.…”
Section: Discussionmentioning
confidence: 57%